Muatan Penyimpangan Sosial dalam Novel Seandainya Aku Boleh Memilih Karya Mira W: Kajian Sosiologi Sastra - Galuh Fatmawati; Maulfi Syaiful Rizal (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This research contains an analysis of the "Seandainya Aku Boleh Memilih" novel by Mira W, which tells of various aspects of life in a civilized environment. In the novel, there are various social problems, so it is fulfilled to research social deviations. Structural functionalism's theory of social deviance sees deviant behavior as a result of social structural pressures. The focus of this research is to describe the manifestations of social deviance behavior and the factors that cause these social deviations, which are constructed in the "Seandainya Aku Boleh Memilih" novel by Mira W. It includes the type of literature research with a qualitative descriptive approach based on the study of the sociology of literature. Data was collected through reading and note-taking techniques which produced data in the form of dialogue or monologue and narration from the data source of the novel entitled "Seandainya Aku Boleh Memilih" by Mira W. This research succeeded in deciphering the types of social deviance from the novel, namely sexual deviance, crime, and lifestyle deviance. While the factors that cause these social deviations are the inability to absorb cultural norms and deviant learning processes.